Morphology of the Undersurface of the Anterolateral Acromion and Its Relationship to Surrounding Structures - Ueda, Yusuke (Orthop J Sports Med, 2021)
BACKGROUND: A better understanding of the morphology underneath the acromion is needed to prevent complications after arthroscopic subacromial decompression. The precise correlations between the morphologic features underneath the acromion and the surrounding structures including the attachment of the coracoacromial ligament (CAL) and the origin of the deltoid middle head have not yet been determined in the absence of artifacts on the bony surface caused by dissection techniques. Moreover, anatomic findings in previous studies using only older-aged cadavers or dried bones may not reflect the morphologic features of younger and healthy specimens. PURPOSE: To characterize the anterolateral structures morphologically in the inferior aspect of the acromion, assess the relationships of these structures with surrounding structures without dissection artifacts on the bony surface, and verify the cadaveric data in the asymptomatic shoulders of living middle-aged patients. STUDY DESIGN: Descriptive laboratory study. METHODS: We initially analyzed the relationship between the morphology of the anterolateral structures and surrounding structures in 18 cadaveric shoulders (mean age, 81.8 years), 15 of which were subjected to macroscopic investigation of the CAL attachment and 3-dimensional micro—computed tomography investigation with radiopaque markers and 3 of which were subjected to histologic examination. We also analyzed the morphology underneath the anterolateral acromion in 24 asymptomatic shoulders of middle-aged patients (mean age, 54.8 years) to verify the cadaveric data. In both the cadaveric shoulders and the asymptomatic shoulders of live patients, the long axis, width, and height of the anterolateral prominence were measured by use of 3-dimensional CT imaging. RESULTS: In cadavers, the anterolateral prominence underneath the acromion corresponded to the attachment of the CAL. Histologic evaluation revealed that the CAL was continuous to the deep layer of the deltoid middle head in the lateral acromion. The study in asymptomatic shoulders of middle-aged patients revealed bony prominences similar to those observed in cadavers. CONCLUSION: The anterolateral prominence, which corresponds to the attachment of the CAL below the acromion, may be a native structure below the acromion. Moreover, the CAL is continuous to the deep layer of the deltoid middle head in the lateral acromion.